One Health in China. Issue 1 (1st January 2016) - Wu, Jianyong; Liu, Lanlan; Wang, Guoling; Lu, Jiahai
Abstract : As a result of rapid economic growth over the previous three decades, China has become the second largest economy worldwide since 2010. However, as a developing country with the largest population, this rapid economic growth primarily based on excessive consumption and waste of resources. Thus, China has been facing particularly severe ecological and environmental problems in speeding up industrialization and urbanization. The impact of the health risk factors is complex and difficult to accurately predict. Therefore, it is critical to investigate potential threats in the context of the human-animal-environment interface to protect human and animal health. The "One Health" concept recognizes that human health is connected to animal and environmental health. This review primarily discusses specific health problems in China, particularly zoonoses, and explains the origin and development of the One Health approach, as well as the importance of a holistic approach in China.